Determination of pesticides in water samples using dispersive liquid – liquid microextraction (DLLME) and gas chromatography- micro electron capture detector (GC-μECD) / Husna binti A Hamid - Husna, A Hamid (2012)
The surface modification of magnetic nanoparticles was carried out in order to change the polarities. The coated particles with octyl group on the surface to ensure the attachment of the functional group and hence improved the extraction process in two step of Dispersive Liquid Liquid Microextraction, DLLME method. Combination of two steps of DLLME method and Gas Chromatography Electron Captured Detector, GC-ECD were used for the extraction and determination of pesticides extracted from water samples (treated waste water, tap water from laboratory and housing area). In this extraction method, CCl4 was selected as the extraction solvent since it shows the highest relative recovery, 41.20 to 98.30 % and 1-octanol was selected as dispersal solvent with the relative recovery of 29.02 to 81.39 %. Under the optimum condition, extraction of pesticides residues in treated waste water, tap water (laboratory and housing area) were investigated. Chlorothalonil in treated waste waters shows the highest content (0.6789 μgL-1) compared tap water in laboratory and hosing area, which lies in the values of 0.4781 and 0.4781 μgL-1 respectively. The presence of DDT residues in three different types of water were detected at the level of 0.1762 to 0.7173 μgL-1. The residue of DDE detected in treated waste water was 0.2122 μgL-1 compared to tap water in housing area (0.1762 μgL-1). However, there are no residues of DDE was detected in tap water collected in laboratory. Chloropyriphos shows the higher percentage recovery compared to the other pesticides residues in the ranges of 43.21 to 86.79 %.